Toward a Clinically Reliable Class II Resin Composite Restoration: A Cross-Sectional Study into the Current Clinical Practice among Dentists in Saudi Arabia - Rasha AlSheikh; Khalid S. Almulhim; Moamen Abdulkader; Rasha Haridy; Amr S. Bugshan; Rand Aldamanhouri; Moataz Elgezawi (Hindawi Limited, 2022)
Objective. The aim of this study was to evaluate the current clinical practice of general dentists in Saudi Arabia in restoring class II cavities using direct resin composites and to set evidence-based practice recommendations of concern. Methods. An online survey formed of 20 questions and classified into four domains was developed. 500 dentists in 5 Saudi provinces were invited to join the survey anonymously and voluntarily using poster announcements and e-mail invitations. Descriptive statistics were used to analyze participants' responses. Results. 343 responses were received. Dentists in Saudi Arabia vary in their clinical practices and techniques of insertion of resin composite in class II cavities. 67% of participants use cotton rolls for isolating the field while 32% use rubber dam isolation. 33% and 28% of respondents use circumferential matrix (Tofflemire) and AutoMatrix, respectively. Fracture, followed by recurrent caries and open proximal contacts, was the received main reason of failure of class II direct resin composite restorations. Conclusion. Diversity of class II resin composite practices exists among dentists in Saudi Arabia. For ensuring optimum quality outcomes and high standards of restorative dentistry healthcare, several dentists in Saudi Arabia need to reconsider their clinical practice and modify their clinical procedures of direct class II resin composites. Several evidence-based practice guidelines are recommended to dentists in this article to improve their practice and enhance the clinical reliability and longevity of class II direct resin composite restorations.